Peer Mentoring Improves Diabetes Technology Use and Reduces Diabetes Distress Among Underserved Communities: Outcomes of a Pilot Diabetes Support Coach Intervention - Jennifer Maizel; Michael J. Haller; David M. Maahs; Ananta Addala; Stephanie L. Filipp; Rayhan A. Lal; Matthew J. Gurka; Lauren Figg; Melanie Hechavarria; Dessi P. Zaharieva; Keilecia G. Malden; Sarah Westen; et al. (Journal of Diabetes Research)
Conclusions: Lower diabetes distress and greater CGM usage among intervention participants suggest that the DSCs’ shared lived experiences and healthcare navigation support positively influenced underserved adults’ outcomes. These findings show DSCs’ potential for improving diabetes care and technology equity.